First aid in Physical Education: an bibliometric review (Research, Society and Development, 2021)
The objective of this study was to analyze the profile of publications on first aid in physical education. The bibliometric method was adopted. The search was conducted between July 2020 and January 2021 at the Virtual Health Library from the Descriptors in Health Sciences in Portuguese: "First Aid" and "Physical Education". Twenty-five publications were identified, selecting 11 of which met the eligibility criteria. The articles were published between 2009-2020, mostly in the Medical Literature Analysis and Retrieval System Online (63.63%; n=7), in English (63.63%; n=7) and in international journals (63.63%; n=7), especially the European Journal of Paediatric Dentistry and Dental Traumatology, with 18.18% (n=2), each. Also, most were from the area of dentistry (72.73%; n=8) and in relation to Qualis Capes, the journals moved between A1 and B4. As for authorship, there were 41 different authors and only one Polish author stood out with two productions (18.18%; n=2). The most cited terms in the titles and descriptors were knowledge (25.0%; n=12), education (22.92%; n=11) and physical education (16.47%; n=8) and the themes worked mainly focused on intervention strategies (100.0%; n=11) and about dental traumas (72.73%; n=8). The findings indicated that there is little knowledge in the area, which requires the need to adoption of educational strategies to qualify professionals and students in the area of physical education in the care of first aid.